2021
DOI: 10.1111/ppl.13452
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐ and tissue‐specific physiological and biochemical changes of two chickpea (Cicer arietinum) varieties following a rapid dehydration

Abstract: In nature, plants may suffer rapid dehydration (RD), which causes significant loss of the annual global chickpea production. Thus, ascertaining more knowledge concerning the RD-tolerance mechanisms in chickpea is crucial for developing high drought-tolerant varieties to assure sustainable chickpea production under sudden water deficit. Here, we focused on genotype-driven variation in leaf relative water content (RWC) and associated differences in RD-responsive physiological and biochemical attributes in roots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…However, plants own an antioxidant system which can keep ROS at non-harmful levels. Some studies have identified a greater action of this system in plants with drought tolerance capacity (Hasanuzzaman et al 2020, Sachdev et al 2021, Salahvarzi et al 2021. The SOD enzyme is the first line of defense of the antioxidant system and has the function of catalyzing the superoxide radical into H 2 O 2 and O 2 (Hassan et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, plants own an antioxidant system which can keep ROS at non-harmful levels. Some studies have identified a greater action of this system in plants with drought tolerance capacity (Hasanuzzaman et al 2020, Sachdev et al 2021, Salahvarzi et al 2021. The SOD enzyme is the first line of defense of the antioxidant system and has the function of catalyzing the superoxide radical into H 2 O 2 and O 2 (Hassan et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Global climate change will undoubtedly affect the frequency and duration of droughts that may destroy forest ecosystems in the future (Salahvarzi et al, 2021). That is why an understanding of the underlying drought tolerance mechanisms of plants is of essential importance, especially in forest tree species.…”
Section: Discussionmentioning
confidence: 99%